Preparation method and application of supported molybdenum nitride catalyst suitable for high-temperature reverse water gas reaction
By adopting the "bottom -up" synthesis strategy in the high -temperature inverse water gas reaction, and directly synthesizing high -decentralized load nitromodoline molybdenum catalysts, the problem of high catalyst cost, poor stability, and low CO selectivity in existing technology. A catalytic effect of high activity and good stability.
Patent Information
- Application Number
- CN202411472360.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The prior art has problems such as high catalyst cost, poor stability and low CO selectivity in high-temperature reverse water gas reactions, making it difficult to achieve efficient CO2 conversion.
The synthetic strategy of "from the bottom up" is adopted, and the precursor of molybdenum salt is highly scattered on the surface of the carrier, and ammonia treatment is performed in the ammonia atmosphere to directly synthesize the high -decentralized load nitrofer molybdenum catalyst.
A high activity and good stability of the load type nitrogen molybdenum catalyst have been achieved. It has excellent hydrogenation effect and catalytic stability. The CO selectivity is higher than 99.9%, and it has broad application prospects in the field of high temperature and water gas.
Smart Images

Figure BDA0005095041360000061 
Figure HDA0005095041370000011 
Figure HDA0005095041370000012
Abstract
Description
(I) Technical field
[0001] The invention relates to a preparation method and application of a high-activity and stable supported molybdenum nitride catalyst suitable for high-temperature reverse water-gas reaction. (II) Background technology
[0002] The catalytic conversion of CO2 is an effective means to alleviate global climate change and marine threats. Among them, the conversion of CO2 into a platform small molecule CO (CO can be synthesized into high value-added chemicals through a mature Fischer-Tropsch process) has important industrial application scenarios (Applied Catalysis B: Environmental, 2021, 284.). Precious metals are considered to be very effective catalysts (Advanced Energy Materials, 2023, 13 (12): 2203806.), but their disadvantages are that they are scarce, expensive, and have poor high-temperature selectivity and stability (Applied Catalysis B: Environmental, 2021, 291: 120101.). However, from the perspective of thermodynamic chemical equilibrium, high temperatures are more conducive to the reverse water-gas shift reaction, and its equilibrium conversion rate will be further improved. Therefore, the development of the reverse water-gas shift reaction at high temperatures has more industrial potential. The most critical of these is the development of efficient catalysts.
[0003] Molybdenum carbide catalysts (Physical Chemistry Chemical Physics, 2022, 24 (27): 16556-16565.) have catalytic properties similar to those of precious metal catalysts and are used in the reverse water gas reaction, but there are problems such as complex preparation methods and low CO selectivity. In addition to molybdenum carbide catalysts, nitride materials recently discovered by Lin et al. (Chinese Journal of Chemical Engineering, 2022, 43: 248-254.), such as molybdenum nitride, also show high CO selectivity in the reverse water gas shift reaction. However, due to the synthesis of a block structure, the specific surface area is small and the active sites are less exposed, resulting in low catalytic activity. Therefore, it is urgent to develop highly dispersed molybdenum nitride catalysts with fully exposed active sites. (III) Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a highly active and stable supported molybdenum nitride catalyst suitable for a high-temperature reverse water gas reaction. The preparation method is simple, low-cost, safe and efficient. This type of catalyst is applied to the CO2 hydrogenation to CO reaction. It has the characteristics of high catalytic activity, good stability and high CO selectivity at high temperatures. It has industrial application prospects in the field of high-temperature reverse water gas, and solves the problems of high cost, poor stability, low CO selectivity and the like in the prior art.
[0005] The technical solution adopted by the present invention is:
[0006] The present invention provides a method for preparing a highly active and stable supported molybdenum nitride catalyst suitable for high-temperature reverse water gas reaction, the method comprising the following steps:
[0007] (1) fully dissolving molybdic acid or molybdate in water to obtain solution A;
[0008] (2) uniformly impregnating the solution A obtained in step (1) on the carrier to form a precursor B;
[0009] (3) Step (2) Precursor B is fully dried at 60-120° C. for 10-15 h to obtain a solid powder;
[0010] (4) The solid powder of step (3) is calcined at 500-800° C. for 1-6 h in an ammonia atmosphere to obtain a highly dispersed supported molybdenum nitride catalyst.
[0011] Furthermore, in step (1), the molybdate is selected from one or more of ammonium molybdate tetrahydrate, ammonium molybdate, and sodium molybdate; and the volumetric amount of water is 1-15 mL / g (preferably 6-9 mL / g) based on the mass of molybdic acid or molybdate.
[0012] Further, the carrier of step (2) comprises silicon dioxide, aluminum oxide, cerium oxide or mesoporous molecular sieve, preferably silicon dioxide or mesoporous molecular sieve MCM-41. The volume amount of solution A is 1-5 mL / g (preferably 2.5 mL / g) based on the mass of the carrier. The loading amount of molybdenum nitride is 20-30% based on the mass of the catalyst.
[0013] Furthermore, step (3) is dried at 80° C. for 12 h.
[0014] Furthermore, in step (4), the ammonia atmosphere is pure ammonia (NH3) or a mixed gas containing ammonia, and the calcination is carried out at 700-800°C for 4-6h.
[0015] The present invention also provides an application of a supported molybdenum nitride catalyst prepared by the method in a high-temperature reverse water gas reaction, wherein the application method is as follows: adding the supported molybdenum nitride catalyst into a fixed bed, introducing a mixed gas of CO2 and H2 (the volume ratio of CO2 to H2 is 1:7-7:10) to complete the process of hydrogenating CO2 to generate CO, the reaction temperature is 200-600°C, and the reaction space velocity is 20000-60000ml / g cat / h, the reaction pressure is normal pressure.
[0016] Furthermore, the volume ratio of CO2 to H2 is 1:3. The reaction temperature is 500-550°C, and the reaction space velocity is 36000-50000 ml / g cat / h.
[0017] Furthermore, the introduction rate of the mixed gas is 70-100 mL / min, preferably 83 mL / min.
[0018] Furthermore, the amount of catalyst added is 2-4 mg / cm 3 .
[0019] Furthermore, the fixed bed is a quartz tube, and preferably the quartz reaction tube has an inner diameter of 8 mm, an outer diameter of 11 mm, and a length of 59 cm.
[0020] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:
[0021] The present invention innovatively adopts a "bottom-up" synthesis strategy, first highly disperses the molybdenum salt precursor on the carrier surface, and then directly performs an ammonia treatment in an ammonia atmosphere without oxidation treatment, thereby achieving a controllable synthesis of small-sized molybdenum nitride, and obtaining highly dispersed molybdenum nitride materials. Compared with the existing method of first oxidizing molybdenum salt to form molybdenum oxide and then performing ammonia treatment to form a bulk molybdenum nitride catalyst, the method of the present invention not only has a simple preparation process and does not require oxidation treatment, but also the obtained molybdenum nitride catalyst is highly dispersed and highly active, and has excellent hydrogenation effect and catalytic stability.
[0022] The catalytic performance of the molybdenum nitride catalyst prepared by the method of the present invention is that a mixture of CO2 and H2 (the volume ratio of CO2 to H2 is 1:3) is introduced at a flow rate of 83 mL / min, the reaction temperature is 550°C, and the reaction space velocity is 50000 ml / g. cat / h, the reaction pressure is normal pressure, the reaction time is 6h, the CO2 conversion rate reaches more than 50%, and the CO selectivity is higher than 99.9%.
[0023] The molybdenum nitride catalyst prepared by the present invention has good high temperature stability. A mixed gas of CO2 and H2 (the volume ratio of CO2 to H2 is 1:3) is introduced at a flow rate of 83 mL / min, the reaction temperature is 550°C, and the reaction space velocity is 50000 ml / g. cat / h, the reaction pressure is normal pressure. After nearly 250h of reaction, the CO2 conversion rate is maintained at 50%, the CO selectivity is above 99%, and it hardly drops, with good high temperature stability.
[0024] The highly dispersed molybdenum nitride catalyst prepared by the method of the present invention has high activity, high CO selectivity and good stability in the reverse water gas shift reaction, and does not lose activity for a long time after repeated cycles. It has broad application prospects in the field of high-temperature reverse water gas. (IV) Description of the drawings
[0025] Figure 1 : XRD pattern (a) and XPS pattern (b) of molybdenum nitride prepared in Example 1.
[0026] Figure 2 : Scanning electron microscope mapping of molybdenum nitride prepared in Example 1.
[0027] Figure 3 : Column chart of CO2 conversion rate and CO selectivity of molybdenum nitride prepared in Example 1.
[0028] Figure 4 : High temperature stability diagram of molybdenum nitride prepared in Example 1 at 550°C.
[0029] Figure 5 : Comparison chart of CO2 conversion rate and CO selectivity of molybdenum nitride and Pt-based catalysts prepared in Example 1.
[0030] Figure 6 : Comparison of CO2 conversion rates at 550°C between the catalyst prepared using a conventional synthesis method and the catalyst prepared in Example 1.
[0031] Figure 7 : XRD pattern of molybdenum nitride prepared in Example 2.
[0032] Figure 8 : Scanning electron microscope mapping of molybdenum nitride prepared in Example 2.
[0033] Fig. 9 : Column chart of CO2 conversion rate and CO selectivity of molybdenum nitride prepared in Example 2.
[0034] Fig.10 : XRD pattern of molybdenum nitride prepared in Example 3.
[0035] Fig.11: Column chart of CO2 conversion rate and CO selectivity of molybdenum nitride prepared in Example 3.
[0036] Fig.12 : XRD pattern of molybdenum nitride prepared in Example 4.
[0037] Fig.13 : Column chart of CO2 conversion rate and CO selectivity of molybdenum nitride prepared in Example 4. (V) Specific implementation methods
[0038] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0039] Example 1. Preparation and performance testing of supported molybdenum nitride catalyst
[0040] 1. Preparation of supported molybdenum nitride catalyst
[0041] (1) Dissolve 300.52 mg of molybdic acid in 2.5 mL of water to obtain 2.5 mL of solution A;
[0042] (2) 2.5 mL of solution A obtained in step (1) was evenly impregnated on 1 g of silica to form precursor B;
[0043] (3) drying the precursor B obtained in step (2) at 80° C. for 12 hours to obtain a solid powder;
[0044] (4) All the solid powder obtained in step (3) was added into a tubular furnace and calcined at 750° C. for 6 hours in an ammonia atmosphere to obtain 1.5 g of a highly dispersed supported molybdenum nitride catalyst, denoted as Mo2N / SiO2, with a particle size of about 10 nm and a molybdenum nitride mass loading of 20%.
[0045] XRD patterns of Mo2N / SiO2, Mo2N, and SiO2 are shown in Figure 1 In a, it can be seen that Mo2N is successfully loaded on the surface of SiO2; the XPS graph of Mo2N / SiO2 is shown in Figure 1 b, proves that the prepared Mo2N / SiO2 contains Mo-N bonds; the scanning electron microscopy mapping of Mo2N / SiO2 is shown in Figure 2 ; In summary, it can be seen that a highly dispersed molybdenum nitride catalyst was successfully prepared.
[0046] 2. Performance Testing
[0047] (1) Effect of different calcination temperatures on catalyst performance
[0048] 0.1 g of the supported molybdenum nitride catalyst prepared in step 1 was loaded into a quartz tube of a catalytic evaluation device (model ICES5F2H, Xiamen Baidewo Intelligent Technology Co., Ltd., the inner diameter of the quartz reaction tube was 8 mm, the outer diameter was 11 mm, and the length was 59 cm). The catalyst dosage was 3 mg / cm based on the effective volume of the fixed bed. 3 A mixture of CO2 and H2 (the volume ratio of CO2 to H2 was 1:3) was introduced at a flow rate of 83 mL / min. The reaction temperatures were 300, 350, 400, 450, 500, and 550 °C, respectively, and the reaction space velocity was 50,000 ml / g. cat / h, the reaction pressure was normal pressure, the reaction time was 6h, and the process of CO2 hydrogenation to CO was completed. The CO2 conversion rate and CO selectivity results are shown in Figure 3 As shown in Table 1, it can be seen that the CO2 conversion rate of the supported molybdenum nitride catalyst prepared in step 1 increases with increasing temperature, and the CO selectivity gradually increases and stabilizes.
[0049] (2) High temperature stability of the catalyst
[0050] The temperature in step (1) was changed to 550°C, and other conditions remained unchanged. The results of CO2 conversion and CO selectivity are shown in Figure 4 As shown, after nearly 250 hours of reaction, the CO2 conversion rate was maintained at 50%, the CO selectivity was above 99%, and it hardly dropped, with good high temperature stability.
[0051] (3) Effect of catalyst type on CO2 conversion
[0052] The reaction temperature in step (1) was changed to 450, 500, 550, and 600°C, respectively, and other operations remained unchanged. Pt / CeO2 (preparation method refers to Journal of Environmental Chemical Engineering, 2020, 8(5): 104236. Optimal conditions) was used as a control. The results are shown in Figure 5 .
[0053] Figure 5 It shows that compared with the precious metal Pt-based catalyst, the CO selectivity of the highly dispersed molybdenum nitride catalyst does not decrease, while the CO selectivity of the precious metal Pt-based catalyst decreases with the increase of reaction temperature. Therefore, the highly dispersed molybdenum nitride catalyst is superior to the Pt-based catalyst.
[0054] Comparative Example 1: Supported molybdenum nitride catalyst synthesized by conventional preparation method
[0055] The supported molybdenum nitride catalyst was prepared by the conventional programmed temperature ammoniation method (prepared under optimal conditions in reference, Wu Zili. Infrared spectroscopy study of simple molecular adsorption and activation on supported molybdenum nitride catalyst [D]. Dalian Institute of Chemical Physics, Chinese Academy of Sciences, 2001.). The performance of the catalyst was far inferior to that of the highly dispersed molybdenum nitride catalyst prepared in Example 1, as shown in Figure 6.
[0056] Example 2: Preparation and performance testing of supported molybdenum nitride catalyst
[0057] 1. Preparation of supported molybdenum nitride catalyst
[0058] (1) Dissolve 300.52 mg of ammonium molybdate in 2.5 mL of water to obtain 2.5 mL of solution A;
[0059] (2) 2.5 mL of solution A obtained in step (1) was evenly impregnated on 1 g of silica to form precursor B;
[0060] (3) drying the precursor B obtained in step (2) at 80° C. for 12 hours to obtain a solid powder;
[0061] (4) All the solid powder obtained in step (3) was added into a tubular furnace and calcined at a constant temperature of 750° C. for 6 hours under an ammonia atmosphere to obtain 1.5 g of a highly dispersed supported molybdenum nitride catalyst with a molybdenum nitride mass loading of 20%.
[0062] XRD pattern Figure 7 From the XRD, it can be seen that the molybdenum nitride catalyst was successfully prepared. The scanning electron microscope mapping image shows that the prepared molybdenum nitride catalyst is highly dispersed, such as Figure 8 shown.
[0063] 2. Performance Testing
[0064] The supported molybdenum nitride catalyst prepared in step 1 was tested under the same conditions as step 2 (1) of Example 1. The results of CO2 conversion and CO selectivity are shown in Table 1. Fig. 9 And as shown in Table 1.
[0065] Example 3. Preparation and performance testing of supported molybdenum nitride catalyst
[0066] 1. Preparation of supported molybdenum nitride catalyst
[0067] (1) Dissolve 300.52 mg of molybdic acid in 1.5 mL of water to obtain 1.5 mL of solution A;
[0068] (2) 1.5 mL of solution A obtained in step (1) was evenly impregnated on 1 g of silica to form precursor B;
[0069] (3) drying the precursor B obtained in step (2) at 80° C. for 12 hours to obtain a solid powder;
[0070] (4) All the solid powder obtained in step (3) was added into a tubular furnace and calcined at a constant temperature of 800° C. for 4 hours under an ammonia atmosphere to obtain 1.4 g of a highly dispersed supported molybdenum nitride catalyst with a molybdenum nitride mass loading of 20%.
[0071] XRD pattern Fig.10 , it can be seen from XRD that the molybdenum nitride catalyst was successfully prepared.
[0072] 2. Performance Testing
[0073] The supported molybdenum nitride catalyst prepared in step 1 was tested under the same conditions as step 2 (1) of Example 1. The results of CO2 conversion and CO selectivity are shown in Table 1. Fig.11 And as shown in Table 1.
[0074] Example 4. Preparation and performance testing of supported molybdenum nitride catalyst
[0075] 1. Preparation of supported molybdenum nitride catalyst
[0076] (1) Dissolve 300.52 mg of molybdic acid in 2 mL of water to obtain 2 mL of solution A;
[0077] (2) 2 mL of solution A obtained in step (1) was evenly impregnated on 1 g of mesoporous molecular sieve MCM-41 to form precursor B;
[0078] (3) drying the precursor B obtained in step (2) at 80° C. for 12 hours to obtain a solid powder;
[0079] (4) All the solid powder obtained in step (3) was added into a tubular furnace and calcined at a constant temperature of 700° C. for 5 hours under an ammonia atmosphere to obtain 1.2 g of a highly dispersed supported molybdenum nitride catalyst with a molybdenum nitride mass loading of 20%.
[0080] XRD pattern Fig.12 , it can be seen from XRD that the molybdenum nitride catalyst was successfully prepared.
[0081] 2. Performance Testing
[0082] The supported molybdenum nitride catalyst prepared in step 1 was tested under the same conditions as step 2 (1) of Example 1. The results of CO2 conversion and CO selectivity are shown in Table 1. Fig.13 And as shown in Table 1.
[0083] Table 1 Conversion rate and CO selectivity of highly dispersed molybdenum nitride synthesized under different conditions
[0084]
[0085] a. Test conditions: CO2:H2=1:3, reaction temperature 550℃, reaction space velocity 50000ml / g cat / h, the reaction pressure is normal pressure, and the control catalyst is prepared by impregnation method (Journal of Environmental Chemical Engineering, 2020, 8(5): 104236.).
[0086] b. Test conditions: CO2:H2=1:3, reaction temperature 450℃, reaction space velocity 36000ml / g cat / h, the reaction pressure is normal pressure, and the control catalyst is prepared by impregnation method (Research on Chemical Intermediates, 2019, 45: 5125-5141.).
Claims
1. A method for preparing a supported molybdenum nitride catalyst suitable for high-temperature reverse water gas reaction, characterized in that: The method comprises the following steps: (1) fully dissolving molybdic acid or molybdate in water to obtain solution A; (2) uniformly impregnating the solution A obtained in step (1) on the carrier to form a precursor B; (3) Step (2) Precursor B is fully dried at 60-120° C. for 10-15 h to obtain a solid powder; (4) The solid powder of step (3) is calcined at 500-800° C. for 1-6 h in an ammonia atmosphere to obtain a highly dispersed supported molybdenum nitride catalyst.
2. The method according to claim 1, characterized in that In step (1), the molybdate is selected from one or more of ammonium molybdate tetrahydrate, ammonium molybdate and sodium molybdate.
3. The method according to claim 1, characterized in that The volumetric dosage of the water is 1-15 mL / g based on the mass of molybdic acid or molybdate.
4. The method according to claim 1, characterized in that The carrier in step (2) includes silicon dioxide, aluminum oxide, cerium oxide or a mesoporous molecular sieve.
5. The method according to claim 1, characterized in that The volume dosage of the solution A in step (2) is 1-5 mL / g based on the mass of the carrier.
6. The method according to claim 1, characterized in that Step (3) Drying at 80°C for 12h.
7. The method according to claim 1, characterized in that The ammonia atmosphere in step (4) is pure ammonia or a mixed gas containing ammonia.
8. The method according to claim 1, characterized in that Step (4) calcining at 700-800°C for 4-6h.
9. Use of a supported molybdenum nitride catalyst prepared by the method of claim 1 in a high-temperature reverse water gas reaction.
10. The use according to claim 9, characterized in that The application method is: adding the supported molybdenum nitride catalyst into a fixed bed, introducing a mixture of CO2 and H2 to complete the process of hydrogenating CO2 to generate CO, the reaction temperature is 200-600°C, the reaction space velocity is 20000-60000ml / g cat / h, the reaction pressure is normal pressure; the volume ratio of CO2 to H2 is 1:7-7:10; the introduction rate of the mixed gas is 70-100mL / min.
Citation Information
Patent Citations
Method for reducing carbon dioxide
CN103025919A
Copper oxide catalyst for preparing isobutene through isobutane dehydrogenation and preparation method and application of copper oxide catalyst
CN104437585A
Catalytic material for water gas shift reaction as well as preparation method and application of catalytic material
CN117884159A
MoOx / Mo2N catalyst for high-temperature reverse water-gas shift reaction and preparation method of MoOx / Mo2N catalyst
CN117943082A
Nitrogen-containing large-specific-surface-area molybdenum-based catalyst for ammonia synthesis and preparation method thereof
CN118179561A